Weak Protection of Geographical Indication Law For Users of Geographically Indicated Goods or Products - Nurlani, Meirina; Emirzon, Joni; Syaifuddin, Muhammad (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Weak protection of geographical indication law owned by users of geographically indicated goods or products cause unfulfilled the rights they deserve. The factors causing it are divided into 2, namely: 1. Weak position owned by users of geographically indicated goods or products. and 2. Weak regulation of law that provide legal protection to users of geographically indicated goods or products.Purposes of the Research: This research aims to analyze and explain factors that cause weak protection of geographical indication law for users of geographically indicated goods or products and also to find out the submission mechanism and procedure of geographical indication infringement lawsuit.Methods of the Research: This study used normative legal research. Research material used primary and secondary legal materials. Data was from library research. Discussion had been collected then processed and analyzed using qualitative approach then at the end of the research, conclusions were drawn using deductive method.Results of the Research: Factors caused weak protection of geographical indication law for geographically indicated users of goods and will provide input for appropriate legal regulations to increase protection of geographical indication law in the future. Furthermore, this also has a positive impact to users of geographically indicated goods and products that they could take legal action against business actors for losses they got in accordance with mechanism and procedure for filling geographical indication infringement lawsuit based on provisions of the applicable law.